ILC1s and ILC3s Exhibit Inflammatory Phenotype in Periodontal Ligament of Periodontitis Patients - Li, Changyi; Liu, Jianyue; Pan, Jie; Wang, Yuhui; Shen, Lei; Xu, Yan (Frontiers in Immunology, 2021)
Innate lymphoid cells (ILCs) are emerging as important players in inflammatory diseases. The oral mucosal barrier harbors all ILC subsets, but how these cells regulate the immune responses in periodontal ligament tissue during periodontitis remains undefined. Here, we show that total ILCs are markedly increased in periodontal ligament of periodontitis patients compared to healthy controls. Among them, ILC1s and ILC3s, particular NKp44+ILC3 subset, are the predominant subsets accumulated in periodontal ligament. Remarkably, ILC1s and ILC3s from periodontitis patients produce more IL-17A and IFN-γ than that from healthy controls. Collectively, our results highlight the role of ILCs in regulating oral immunity and periodontal ligament inflammation and provide insights into targeting ILCs for the treatment of periodontitis.